Trade Relations of the Population of the Far North in the 11th – 14th Centuries - Kardash Oleg V.; Gaidakova Zoia G. (Поволжская археология, 2020)
The economic factor always has a significant impact on any nation culture formation processes and is mostly pronounced in trade. Until recently, the main sources for investigating this area of the economy were fragmentary chronicles of Ugra and individual finds of imported luxury items – the works of medieval Oriental and Russian master jewelers. The paper presents the results of excavations of the archaeological layer of the beginning of the 13th – early 14th century of Bukhta Nakhodka settlement and Bukhta Nakhodka 2 burial site. On the basis of materials obtained, the authors investigated the volumes and directions of trade and exchange processes of Ugra population in the 13th – 14th centuries. The authors also determined that the Novgorod Republic was a predominant direction for trade and economic relations of the inhabitants of the South of Yamal Peninsula.